MULTI CRITERIA DECISION MAKING: A CASE OF LOCATING LOW COST CARRIER TERMINAL (AIR) IN MALAYSIA (Journal of Technology and Operations Management, 2015)
Decision making is an important rule to an individual or a group within an organization. However, decision making can sometime take a long time to be realized. The objective of this paper is to investigate if a different approach that is the Analytic Hierarchy Process (AHP) model is applicable in facilitating decision making, particularly for decision makers who were faced with multiple criteria problems. In this paper, a group of decision makers (judgement sampling were used) were tasked to determine the location for the operation of low-cost carrier comprising sites of which include the KLIA, Subang Airport and the Low-Cost Terminal. The AHP was used as a decision making approach to observe if it is applicable in addressing the multiple criteria decision making problems. The criteria that are taken into consideration in this study include the benefit and cost of each selected location in terms of economy, social and environment. The AHP allows decision to be constructed as hierarchies and each criterion can be assigned to a preference scale that is determined by the decision makers. The findings indicate that the approach facilitates decision making in a shorter period of time. In general, based upon the preference scale assigned by decision-makers to the identified criteria the Low-Cost Terminal is highly preferable with an economic ratio benefit of 0.447 and social ratio benefit of 0.437. However, in terms of environmental benefits with a ratio of 0.508, the KLIA was preferred by the decision makers over Subang Airport and the Low-Cost Terminal. Overall, the Low-Cost Terminal is highly preferred with a ratio of 0.719, 0.488 and 0.454 for each criterion.